Amerika Siyasi Tarihinde Başkan Martin Van Buren ve Döneminde İzlenilen İç-Dış Politikanın Analizi - Kaya, İbrahim; Koç, Engin (Muş Alparslan Üniversitesi, 2021)
Martin Van Buren is the first president, who was born in the independent United States and first non-British origin among the presidents at the sametime. Martin Van Buren, the eighth president of the White House, became a lawyer and his interest in politics began very early age. The political life of Van Buren, which started as a delegate in the provincial congress in 1800, was ended Free Soil in 1848, and with the campaign to prevent the spread of slavery. Van Buren, who served as governor, deputy, senator, foreign minister, vice president and eventually president in American politics, he has struggled with important events is in terms of American history such as the panic of 1837, the determination of America's borders, the issue of preventing the spread of slavery, the annexation of Texas, the integration of the natives into the central government. In this study, will be examined Martin Van Buren's early political life, the process of being elected president, domestic and foreign political developments that are vital for the United States during his presidency. In order to create a whole in this study, brief information about American Political History will be presented until Van Buren's presidency.

Martin Van Buren, bağımsız Amerika Birleşik Devletlerinde doğan ilk ve aynı zamanda İngiliz kökenli olmayan ilk başkandır. Beyaz Saray’ın sekizinci başkanı olan Martin Van Buren bir hukukçu olmak ile birlikte onun siyaset ile ilgisi oldukça genç yaşlarda başlamıştır. Van Buren’in 1800’de eyalet kongresinde delege olarak başlayan siyasi hayatı 1848 yılında Free Soil olarak isimlendirilen, köleliğin yaygınlaşmasını önleme kampanyası ile son bulmuştur. Amerika siyasetinde valilik, vekillik, senatör, dış işleri bakanı, başkan yardımcısı ve nihayet başkanlık görevlerini icra eden Van Buren 1837 Paniği, Amerika’nın sınırlarının belirlenmesi, köleliğin yaygınlaştırılmasını engelleme meselesi, Teksas’ın Birleşik Devletlere kabulü meselesi, yerlilerin merkezi hükümete entegrasyonu gibi Amerika tarihi açısından önemli olaylar ile mücadele etmiştir. Bu çalışmada Martin Van Buren’in erken dönem siyasi hayatı, başkan seçilme süreci, başkanlık döneminde Amerika Birleşik Devletleri açısından hayati öneme sahip iç ve dış politik gelişmeler irdelenecektir. Çalışmanın bir bütün oluşturması ve kopuklukları ortadan kaldırmak adına, Van Buren’in başkanlık dönemine kadar Amerikan Siyasal Tarihi hakkında özet bilgi sunulacaktır.
Analysis of the Domestic-Foreign Policy Followed by President Martin Van Buren’s Period in American Political History
anemon
Keywords: Martin van buren; American political history; Slavery; Annexation of Texas; Martin Van Buren; Kölelik; Amerikan siyasi Tarihi; Teksas’ın İlhakı